Photoreceptor disruption in central serous chorioretinopathy treated by half-dose photodynamic therapy - Ratanasukon M (Dove Medical Press, 2013)
Mansing Ratanasukon, Koblarp Thongthong, Patama Bhurayanontachai, Pichai JirarattanasopaDepartment of Ophthalmology, Faculty of Medicine, Prince of Songkla University, Hat yai, Songkhla Province, ThailandBackground: To evaluate photoreceptor disruption in patients with central serous chorioretinopathy (CSC) treated by half-dose photodynamic therapy (PDT).Methods: A total of 29 patients with symptomatic CSC were recruited and underwent half-dose verteporfin PDT covering the leakage sites as observed via fundus fluorescein angiography. The primary outcome was the percentage of patients with the presence of photoreceptor disruption, and the secondary outcome was the correlation between photoreceptor disruption and visual results at the 1-year follow-up.Results: Photoreceptor disruption was identified in 13 eyes (44.8%) 12 months after treatment. Twenty-seven patients experienced best-corrected visual acuity (BCVA) improvement after PDT, while two patients showed stable BCVA. The mean BCVA in patients with photoreceptor disruption at the baseline and every follow-up visit was significantly lower than that of patients without photoreceptor disruption. However, there was no correlation between the presence or absence of photoreceptor disruption and the improvement of visual acuity because the BCVA gain at the last follow-up visit between the two groups was not significant (P = 0.69). No potential ocular complication was encountered in the study.Conclusion: Photoreceptor disruption was found in about 45% of CSC patients treated by PDT, which ultimately resulted in poor visual outcomes. However, a half-dose PDT might not affect or modify the photoreceptor function because it gave the same pattern of visual recovery in patients with and without photoreceptor cell loss.Keywords: photoreceptor disruption, central serous chorioretinopathy, photodynamic therapy